PENINGKATAN KAPABILITAS DINAMIS UNTUK USAHA BERKELANJUTAN TOKO AROFAH - Ghoniyatut Toyyibah; Aries Kurniawan (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study aims to determine the sustainability of Toko Arofah's business and to find out the dynamic capabilities possessed by the first generation to the second generation in continuing the business. The form of research used is qualitative research. The research was conducted at Toko Arofah which is located at Jalan Raya Mojopuro, Babatan Village, Balongpanggang District, Gresik Regency. Data collection techniques with observation, interviews and documentation. The research subjects were one business owner, one next generation, three suppliers, and five customers. The results of this study are that the sustainability of Toko Arofah's business can be achieved through the ability to adapt to changing times, flexibility in facing challenges, and investment in modern technology. Also, Toko Arofah's dynamic capabilities lie in the application of sensing capabilities to identify opportunities and threats from the external environment, development capabilities help turn these opportunities into strategic actions. Furthermore, transformation capabilities ensure that the company can adjust and reconfigure existing resources to deal with changes and strengthen its competitive position.